If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3p-10=-10(-4p+9)-5(-2+9p)
We move all terms to the left:
-3p-10-(-10(-4p+9)-5(-2+9p))=0
We add all the numbers together, and all the variables
-3p-(-10(-4p+9)-5(9p-2))-10=0
We calculate terms in parentheses: -(-10(-4p+9)-5(9p-2)), so:We get rid of parentheses
-10(-4p+9)-5(9p-2)
We multiply parentheses
40p-45p-90+10
We add all the numbers together, and all the variables
-5p-80
Back to the equation:
-(-5p-80)
-3p+5p+80-10=0
We add all the numbers together, and all the variables
2p+70=0
We move all terms containing p to the left, all other terms to the right
2p=-70
p=-70/2
p=-35
| 57=14.x | | 2x+3=6+1x | | 4x=6x+32 | | 8a+2/5-1=10a-3/5 | | -3+8y=45 | | -3x+2-1=3x | | 5(2x-1)=115 | | 5a−15+9a=3a+29 | | −36+2x=−8x+x | | 1/2(2x-4)+2x=13 | | -10-(-4x-8)=2(x+4) | | 3(j-17)=6 | | -7(8x+4)=-308 | | 12=2(y-15)+6 | | 9m-10+5m-15+4m=65 | | 2(5x+9)=-11+9 | | –4(p−67)=–36 | | 0=-10+10k | | 5(-10r+6)+20r=-4(9r-15) | | 7=x^2-12x | | 4(2x+8)=48+72 | | -20+40=40x+20 | | -3x+10+8x+10x=-35 | | 2(-2x+1)-5x+2=−23 | | 3(x+4)=8x-12 | | 15+5x=21+3x | | 8z-Z=7-35 | | -7(9s-19)=-14s-14 | | 12+3x=6x+3 | | -3(x-16)+2+4x=54 | | 80=6h-35 | | 3(r+3)+1=19 |